An Improved `DC-DC Type' High Frequency Transformer-Link Inverter by Employing Regenerative Snubber Circuit - Salam, Zainal; Ayob, S.M; Ramli, Mohd zulkifli; Azli, N.A (2007)
This work proposes a bidirectional high frequency (HF) link inverter using center-tapped high frequency transformer. The main advantage of this topology is the reduced size of the converter. However the utilization of the high frequency transformer results in the occurrence of high voltage spike at its secondary. To solve this problem, we incorporate a regenerative snubber to clamp the spike and subsequently feed the energy back to the power circuit. The inverter also utilizes less number of switches, which results in lower conduction and switching losses. This paper describes some of the important aspects of the snubber design. It is verified with a 1 kW inverter prototype